MYBL2-Driven Transcriptional Programs Link Replication Stress and Error-prone DNA Repair With Genomic Instability in Lung Adenocarcinoma - Morris, Benjamin B.; Wages, Nolan A.; Grant, Patrick A.; Stukenberg, P. Todd; Gentzler, Ryan D.; Hall, Richard D.; Akerley, Wallace L.; Varghese, Thomas K.; Arnold, Susanne M.; Williams, Terence M.; Coppola, Vincenzo; Jones, David R.; et al. (Frontiers in Oncology, 2021)
It has long been recognized that defects in cell cycle checkpoint and DNA repair pathways give rise to genomic instability, tumor heterogeneity, and metastasis. Despite this knowledge, the transcription factor-mediated gene expression programs that enable survival and proliferation in the face of enormous replication stress and DNA damage have remained elusive. Using robust omics data from two independent studies, we provide evidence that a large cohort of lung adenocarcinomas exhibit significant genome instability and overexpress the DNA damage responsive transcription factor MYB proto-oncogene like 2 (MYBL2). Across two studies, elevated MYBL2 expression was a robust marker of poor overall survival and disease-free survival outcomes, regardless of disease stage. Clinically, elevated MYBL2 expression identified patients with aggressive early onset disease, increased lymph node involvement, and increased incidence of distant metastases. Analysis of genomic sequencing data demonstrated that MYBL2 High lung adenocarcinomas had elevated somatic mutation burden, widespread chromosomal alterations, and alterations in single-strand DNA break repair pathways. In this study, we provide evidence that impaired single-strand break repair, combined with a loss of cell cycle regulators TP53 and RB1, give rise to MYBL2-mediated transcriptional programs. Omics data supports a model wherein tumors with significant genomic instability upregulate MYBL2 to drive genes that control replication stress responses, promote error-prone DNA repair, and antagonize faithful homologous recombination repair. Our study supports the use of checkpoint kinase 1 (CHK1) pharmacological inhibitors, in targeted MYBL2 High patient cohorts, as a future therapy to improve lung adenocarcinoma patient outcomes.